The relationship between reaction time and 60 m performance in elite athletes - Gürses, V. V.; Kamis, O. (Journal of Education and Training Studies, 2018)
The aim of this study was to investigate the relationship between 60m sprint results and reaction times in athletes who took part in the World Indoor Athletics Championships. The reaction times and 60m sprint results were compiled for 483 sprinters (253 male, 230 female) who performed 60m sprint event. Corresponding data were obtained from archives of the official website of the International Association of Athletics Federation (IAAF). The relationship between reaction time and 60m sprint results were calculated using Pearson correlation coefficient. Additionally, the Independent Samples T-Test was used to compare athletes` reaction times and 60m sprint results. Positive moderate correlation was found between mean values of all 60m sprint results and reaction times, which were analyzed together in all categories (r=.436, p<0.01). Moreover, significant differences were also found between male and female finalists based on the 60m sprint times and reaction times respectively (t=-27.98, p<0.01; t=-3.26, p<0.01). As a result, it can be concluded that reaction time has great importance on 60 m performance. The best reaction time is related to the higher performance of 60m sprint in both male and female athletes. Moreover, this is also similar for round 1, semifinal and final categories. Coaches and athletes may consider improving reaction time to achieve better 60m performance.